The monsterologist : a memoir in rhyme - Katz, Bobbi (Sterling Pub. Co., 2009)
"The world's foremost expert in monsterology shares his rare collection of letters, notes, and memorabilia ... [including] an interview with the Loch Ness monster, an invitation from Count Dracula, Bluebeard's personal ad, and many other monstrous secrets"--P. [4] of cover.